Electromagnetic field equations securing state weightlessness - Smolyakov Eduard (EPJ Web of Conferences)
In this work, using the “Extreme Theory of Dimensions”, hitherto unknown differential equations of field theory are obtained, which make it possible to ensure the movement of massive bodies using a sufficiently strong electromagnetic fields, which will become available in the near future. It is most likely that the builders of the Egyptian pyramids moved huge stone blocks using an electromagnetic field. The equations found can also be used to develop electromagnetic accelerators to replace the first stage of large multistage rockets.